Epistaxis: a retrospective clinical study - ., Shaweta; Sharma, Rajnish; Sharma, Nisha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Epistaxis is one of the common emergencies in otorhinolaryngology. The aims and objectives of present work were to study incidence of epistaxis, etiological factors responsible for epistaxis and management of epistaxis. Methods: A retrospective study (February 2019 to March 2020) of patients admitted in department of otorhinolaryngology with complaint of nasal bleeding was done. The study was conducted on 96 patients for the incidence, age and sex relation, etiological factors, clinical findings and treatment methods for epistaxis. Results: Out of the total 96 cases of epistaxis, 58.3% were males and 41.6% were females. Most of the patients were over 40 years of age. The maximum, 19 (19.79%) were in the age group of 51-60 years and minimum, 2 (2.08%) were in the age group of 90-100 years. In the study of 96 cases, common group in this series was of cardiovascular causes (hypertension, arteriosclerosis, on antiplatelet drugs), 59 cases (61.45%), out of 59 cases, 9 patients were on antiplatelet drugs followed by idiopathic cases 13 (13.54%), trauma 12 (12.5%), 7 cases (7.29%) blood dyscrasias, spur with DNS 3 (3.12%), infection 1 (1.04%), alcoholic liver disease 1 (1.04%). Out of 96 cases, 92 cases (95.8%) responded to nonsurgical methods. Conclusions: Epistaxis can be seen in any age. Hypertension, trauma and coagulopathy were the most common etiological factors. Anterior nasal packing was the most common treatment method applied to these patients.